Prevalence of the Helicobacter pylori babA2 Gene in Children Mainly Depends on the PCR Primer Set Used - Anja Šterbenc; Maja M. Lunar; Matjaž Homan; Boštjan Luzar; Nina Zidar; Mario Poljak (Canadian Journal of Infectious Diseases and Medical Microbiology)
Various polymerase chain reaction- (PCR-) based methods with varying positivity rates were designed to detect the Helicobacter pylori babA2 gene. To compare different primer sets, babA2 prevalence was determined in 279 H. pylori-positive pediatric samples using the 832 bp, 139 bp, and 271 bp PCR primer sets, resulting in 34.0%, 51.3%, and 79.6% prevalence of the babA2 gene, respectively. The babA2 status determined using the 832 bp and 139 bp PCR primer sets significantly correlated with bacterial density and activity of inflammation, whereas no such correlations were found using the 271 bp PCR primer set. The 139 and 832 bp PCR primer sets concordantly detected the babA2 gene in 93 cases; however, in comparison to the 832 bp PCR primer set, the 139 bp PCR primer set detected additional 50 babA2 cases, whereas only two 832 bp positive cases were missed. The 271 bp PCR primer set missed 32 babA2 cases that were 832 bp and/or 139 bp PCR positive, but tested solely positive in 109 cases. Interestingly, cloning of a subset of 271 bp PCR positive samples revealed amplification of the babA/B gene chimera. Hence, in our opinion, the 271 bp PCR protocol is not a reliable diagnostic tool for detecting the babA2 gene in children. Our results reaffirm previous observations that the use of certain babA2 PCR primer sets can significantly impact estimation of the prevalence and clinical relevance of the H. pylori babA2 gene in children, suggesting babA2 detection methods should be carefully selected.